Pengaruh Kartu Debit, Kartu Kredit dan E-Money terhadap Inflasi di Indonesia - Audry Melisa Margareta Sijabat; Etik Umiyati; Dwi Hastuti (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analyze the development of debit card, credit card, and e-money usage and inflation in Indonesia, while also examining the effect of these three payment instruments on inflation from January 2015 to July 2025. The method used is the Error Correction Model (ECM) with the help of Eviews 12 software, while data was obtained from Bank Indonesia (BI) and the Central Statistics Agency (BPS). The results show that in the long term, debit cards do not have a significant impact on inflation. Conversely, credit cards have a positive and significant impact, indicating that increased credit card usage can drive up inflation. On the other hand, e-money has a negative and significant effect on inflation in the long term, so that increased e-money transactions actually tend to suppress inflation. In the short term, these three payment instruments—debit cards, credit cards, and e-money—do not show a significant impact on inflation in Indonesia. These findings provide insight into the dynamics of non-cash payment instruments and provide assurance regarding price stability.